Ibn Hisham ’s efforts in Al- Balajah to explain Bant Souad - Al-Ruwais, Abdullah Saad Mohammed (Arab Journal for Sciences and Research Publishing, 2018)
This research sheds light on the rhetorical aspects of the son of Hisham’s grammar (761 h), by explaining his heel poem ibn Zuhair ibn Abi Salma (t. 26h), one of the most beautiful poems spoken in the hands of the Prophet (peace and blessings of Allaah be upon him). This study revealed the efforts of Ibn Hisham in the three eloquence sciences: meanings, statement and exquisite. In the case of semantics, the news is created, and the information is kept, and the communication is restricted, the caution, the attention, the nails, the refining and the metaphor. As far as the science of the statement is concerned, the son of Hisham mentioned some of the similarities; With regard to the eloquent analogy, he referred to it in his commentary and identified some of the subject matter, and his distinction with the metaphor was a transmission of the rhetoric. In the case of fat benefactors, Hisham’s son referred to some as anagram, Sajaa and studs. By researching the many rhetorical applications that Ibn Hisham used to reveal the beauty of this poem. The search revealed the return of Hisham’s son to the scholars of eloquence, citing their evidence in their works.